Communicative Self-confidence and Motivation: An Educational Experience of Linguistic Immersion and Leisure in Nature - Julio Fuentesal-García; Alba González-Peño; Anna García-Hernández; Evelia Franco (Journal on Efficiency and Responsibility in Education and Science)
Communicative self-confidence and motivation play a crucial role in learning any language, including English. The absence of these elements significantly impacts students' ability to express themselves naturally and fluently. In Spain, language immersion programs seek to promote the simultaneous learning of language skills in a communicative context, facilitating learners' proficiency development. This study focuses on analyzing the influence of the natural environment and leisure activities on learning English as a second language (L2), investigating whether participation in a language immersion program in nature improves learners' communicative self-confidence and whether they perceive greater empowerment compared to conventional English classes. Participants were 305 students of Secondary Education, of whom 172 were female. Results indicate that students who participated in the language immersion program experienced significant improvements in their communicative self-confidence and perceived greater relatedness support (Z=-3.55; p < .001; δ = -.21 and Z=-5.26; p < .001; δ = -.32, respectively). These findings highlight how the natural environment provides a conducive environment for the development of communicative and social skills, reducing language anxiety and improving students' self-confidence, and points to the importance of exploring basic psychological needs to understand the interaction between students, teachers, and environment in the process of learning English.